Pemanfaatan Tepung Kulit Udang sebagai Bahan Pengganti Pakan Jadi untuk Pertambahan Berat Itik Pedaging - Wahyu Trianto; Tuntas Bagyono; Abdul Hadi Kadarusno (Poltekkes Kemenkes Yogyakarta, 2017)
Ducks as meat source in Indonesia, based on 2010 statistics data, only fulfill 44,75 % of the 14,3thousand ton demand. On the other hand, the waste of shrimp shell can be utilized as additional substance for duck feed. This study was aimed to understand the influence of shrimp shell flour (i.e. 0 % as the control, 10 %, 12 % and 14 %) used in the feed on the weight growth of ducks. The study was conducted in Jarakan Village of Ceporan, Gantiwarno, Klaten Regency and employed a pre-test post-test with control group designed quasi experiment. The study object was 60 ducks aged 0-5 days, meanwhile the shrimp waste were obtained from restaurants at Rawa Jimbung. Each mixture feed was given to 15 ducks which were placed at different pens, as muchas 150 gr/week/duck twice a day. The data were analysed by using one way anava at ? = 0,05; and obtained p-value less than 0,001 which means that the difference of the weight increase among the treatment variation is statistically significant. It can be interpreted that the variations of shrimp shell flour addition do influence the weight of the ducks. The subsequent LSD test concluded that 14 % concentration of shrimp waste is the most effective.